Millie's fling ebook - Mansell, Jill (2009)
Millie's quiet, single summer is about to get turned upside down... When her dear friend and bestselling novelist Orla Hart invites Millie to spend the summer with her in Cornwall, Millie leaps at the chance to spend the summer alone, recovering from a bad breakup. But Orla has other ideas. Envisioning Millie as the heroine of her next novel, Orla is determined that Millie should meet the man of her dreams this summer. The trouble is, Millie's taste in men doesn't match with Orla's at all. Hugh Emerson, dashing young widower, is the one who really interests her. He is also the one man Orla insists she shouldn't get involved with. With dropped wallets, rollerskating gorillagrams, the world's most flirtatious boss, and a helicopter in the back garden, It's sure to be an unforgettable summer... A fresh and fun British women's fiction and a great romantic book with plenty of humor, friendship, and some madcap fun. Fans of Meg Cabot, Sophie Kinsella, Helen Fielding and Jennifer Weiner will want to escape to Cornwall this summer to find their own romance. What reviewers are saying about Millie's Fling: "Millie's Fling is a super cute and wicked funny book and I thoroughly enjoyed myself while reading it. "—Night Owl Romance "Readers will find a CHARMING ROMP in Jill Mansell'sMillie's Fling."—BookPage "Ms. Mansell creates such likable and heartwarming characters (like Millie and Orla) that the reader can't help but root for them."—Booking Mama "Millie's Fling is a feel-good book for chick lit fans or readers looking for a light and funny novel packed with memorable characters."—Diary of an Eccentric